The Ising model on random lattices in arbitrary dimensions - Bonzom, Valentin; Gurǎu, Rǎzvan; Rivasseau, Vincent (Physics letters, 2012)
We study analytically the Ising model coupled to random lattices in dimension three and higher. The family of random lattices we use is generated by the large N limit of a colored tensor model generalizing the two-matrix model for Ising spins on random surfaces. We show that, in the continuum limit, the spin system does not exhibit a phase transition at finite temperature, in agreement with numerical investigations. Furthermore we outline a general method to study critical behavior in colored tensor models.
Gesehen am 30.09.2022